Making a Living. Consumption Dynamics in Poor Neighborhoods in Buenos Aires and Rio de Janeiro from a Female Perspective - Micaela Diaz Rosaenz (Iberoamericana. América Latina - España - Portugal)
This article explores the social implications and meanings associated with consumer spending on private goods and the circulation of different forms of money in poor neighborhoods. The research is based on a qualitative methodology with in-depth interviews with women heads of household in a poor neighborhood in the city of Buenos Aires and Rio de Janeiro. The research shows that, contrary to common criticisms about poor management and lack of foresight in low-income sectors, families employ careful planning to manage their resources, navigating contradictory expectations of thrift and economic sufficiency, even in the face of unforeseen events.